Introduction to Microbiome - Fuloria, Shivkanya; Vetriselvan, Subramaniyan; Mahendran, Sekar; Wu, Yuan Seng *; Srikumar, Chakravarthi; Rusli, Bin Nordin; Sharma, Pradeep Kumar; Meenakshi, Dhanalekshmi Unnikrishnan; Mendratta, Ajay; Fuloria, Neeraj Kumar (Springer Singapore, 2022)
The microbiome is the indigenous microbial population (microbiota) and the host environment in which it lives, and it is revolutionising how doctors think about germs in human health and illness. The understanding that most microbes in human bodies perform vital ecosystem functions that benefit the whole microbial host system is perhaps the most basic development. The microbiome is a collection of varied and numerous bacteria that live in the gastrointestinal system. Generally, this ecosystem comprises billions of microbial cells that play a vital role in human health control. Immunity, nutrition absorption, digestion, and metabolism have all been linked to the microbiome. Researchers have discovered that changes in the microbiome are linked to the development of diseases including obesity, inflammatory lung disease, and CVS diseases, carcinoma in recent times. A change in the microbial population of the intestine has a big impact on human health and disease aetiology. These changes are caused by a combination of factors, including lifestyle and the existence of an underlying illness. Dysbiosis makes the host more susceptible to infection, the type of which varies depending on the anatomical location. The distinct metabolic processes and roles of these bacteria inside each bodily location are accounted for by the inherent variety of the human microbiota. As a result, it is critical to comprehend the human microbiome’s microbial makeup and behaviours as they relate to health and illness.